Are school leaders working as instructional leaders? Exploration of school leadership practices in rural Pakistan - Tooba Noor; Ali Nawab (Cogent Education, 2022)
School Leadership is widely acknowledged as a prime determiner of school improvement. Among the various leadership models, Instructional Leadership (IL) is considered as having greater impact upon the school, teachers, and student achievement. Consequently, an increasing attention has been paid to IL across the globe. However, we lack any empirical evidence regarding how IL unfolds in rural contexts characterized by many challenges. Hence, this research explores IL practices in a secondary school in rural Sindh, Pakistan. Data are collected from school leaders and teachers through focused group and semi-structured interviews, observations of leadership practices and document analysis. The findings of the study revealed that school leaders played restricted role as instructional leaders (ILs). Their priorities were more administrative and managerial related tasks rather than student achievement, teachers’ professional development (PD) and creating learning culture as suggested in educational literature. The outcomes of this research provoke thoughts in relation to school leadership in the developing world especially in rural contexts having significant implications for policy makers, educational reformers and school leaders.